2017
DOI: 10.21106/ijma.186
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Combined Mother-Infant Clinic to Optimize Post-Partum Maternal Retention, Service Utilization, and Linkage to Services in HIV Care in Rural Rwanda

Abstract: Background and Objectives:Despite recent improvements in accessibility of services to prevent mother-to-child transmission of HIV, maternal retention in HIV care remains a challenge in the post-partum period. This study assessed service utilization, program retention, and linkage to routine services, as well as clinical outcomes for mothers and infants, following implementation of an integrated mother-infant clinic in rural Rwanda.Methods:We conducted a retrospective cohort study of all HIV-positive mothers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…In a prospective study conducted in Rwanda, a higher impact was reported where modern contraception prevalence of 72% was found following service integration intervention compared to 30% before the intervention. [25] In our multivariate analysis that combined HIV-positive and negative women (Model 1), HIV-positive status awareness increased the odds of modern contraceptives by 48%. In HIV-positive women (Model 2), being on integrated service increased the odds of modern contraceptives by 85%.…”
Section: Discussionmentioning
confidence: 80%
“…In a prospective study conducted in Rwanda, a higher impact was reported where modern contraception prevalence of 72% was found following service integration intervention compared to 30% before the intervention. [25] In our multivariate analysis that combined HIV-positive and negative women (Model 1), HIV-positive status awareness increased the odds of modern contraceptives by 48%. In HIV-positive women (Model 2), being on integrated service increased the odds of modern contraceptives by 85%.…”
Section: Discussionmentioning
confidence: 80%
“…The MCH-ART trial demonstrated improved maternal engagement and virologic suppression with the MCH-ART intervention compared to the standard of care [8]. Other studies have demonstrated a similar, positive effect of integrated services on retention, but to our knowledge, MCH-ART is the first to show improvement in both retention and virologic suppression [39, 40]. Our results demonstrate that, in addition to being clinically effective, the MCH-ART intervention is cost-effective, with an ICER of $599/YLS.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive approach to the mother–infant pair’s health needs during the breastfeeding period is promising for this population. Guillaine et al 22 describe the success of a “Combined Clinic” in Rwanda, which provided maternal and infant care, including regular home visits and nutritional supplementation, until the child was 18 months of age; in this program no mothers were lost to follow-up during breastfeeding and 95% of HEI received HIV testing. Successful “mother–infant pair” clinics have incorporated innovative approaches, such as text message reminders, and have relied on a comprehensive approach to encourage retention and linkage.…”
Section: Service Delivery Modelsmentioning
confidence: 99%